Study on the passively mode-locked soliton fibre lasers - Ang, Soo Ling (2009)
An optical fiber is made of glass or plastic which carries light along its length. Light is kept in the core of the optical fiber by total internal reflection. The use of optical fiber as the gain medium of a laser has many advantages due to its low cost, lightweight and flexible. In 1965, Norman Zabusky and Martin Kruskal observe using numerical simulation of the KDV (Korteweg–de Vries) waves that pass through each other without altering shape and speed. This phenomenon was described by the term “soliton”. There are two main types of soliton, namely spatial solitons and temporal solitons. Spatial soliton is formed when the nonlinearity effect balances the light diffraction in the medium. Temporal soliton occurs when the non-linearity effect balances the dispersion of an optical pulse. Apart from the above, vector soliton are solitons with more than one optical fields. In 1987, dark soliton characterized as a dip in the light intensity profile against a uniform background was observed. In this report, the dark soliton propagation in the laser cavity was studied intensively. A fibre laser model was numerically setup to simulate the operation of an erbium doped ring cavity laser mode-locked with the saturable absorber incorporating nanotube (SAINTs) or nonlinear polarization rotation (NPR) technique. The Matlab is used to plot the generated data to study the intensity and spectrum profiles. The effects of increasing gain with a fixed beat length by adding or removing the saturable absorber effect was discussed. By setting the gain-guided soliton to achieve the dark soliton, whereby changing parameters such as the step size (Dz) and linear cavity phase delay bias (Ph) was analysis.